Exploring Cultural Values, Dynamic Capabilities, and Organizational Performance in Family-Owned Paint Manufacturing Companies - Erwin Widjaja; Achmad Setyo Hadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Family businesses in Indonesia’s paint manufacturing industry face intense competition, increasing demands for innovation, and dynamic regulatory pressures that require balancing cultural value preservation with the development of adaptive capabilities. This study aims to explore the relationship between organizational cultural values, dynamic capabilities, and organizational performance within the context of family businesses, with a particular focus on the subjective experiences of leaders. The research employs a qualitative interpretative phenomenological approach (Interpretative Phenomenological Analysis/IPA) through case studies of two family-owned paint manufacturing companies, collecting data via in-depth interviews with CEOs and conducting thematic analysis of interview transcripts. The findings reveal that core cultural values such as family loyalty, trust, harmony, and long-term orientation serve as the foundation for building sensing, seizing, and reconfiguration capabilities that enable firms to adapt to market and regulatory changes. The integration of cultural values and dynamic capabilities has been shown to drive revenue growth, operational efficiency, customer satisfaction, and sustainable competitive advantage. The study concludes that the synergy between organizational cultural values and dynamic capabilities not only determines the performance success of family businesses but also strengthens strategic resilience in competitive traditional industries. Theoretically, this research enriches the understanding of how cultural value–capability integration operates within the Resource-Based View framework, while practically it offers managerial recommendations for family businesses to maintain a balance between cultural heritage and innovation for long-term sustainability.